Levels of Interferon-Gamma Increase after Treatment for Latent Tuberculosis Infection in a High-Transmission Setting - Iukary Takenami; Brook Finkmoore; Almério Machado; Krisztina Emodi; Lee W. Riley; Sérgio Arruda (Pulmonary Medicine)
Objectives. We investigated IFN-γ levels before and after a six month course of isoniazid among individuals with latent tuberculosis infection (LTBI) in a high-transmission setting. Design. A total of 26 household contacts of pulmonary tuberculosis patients who were positive for LTBI by tuberculin skin test completed six months of treatment and submitted a blood sample for a follow-up examination. The IFN-γ response to Mycobacterium tuberculosis-specific antigens was measured, and the results before and after the completion of LTBI treatment were compared. Results. Of the 26 study participants, 25 (96%) showed an IFN-γ level higher than their baseline level before treatment (P≤0.001). Only one individual had a decreased IFN-γ level after treatment but remained positive for LTBI. Conclusion. In a high-transmission setting, the IFN-γ level has increased after LTBI treatment. Further studies must be undertaken to understand if this elevation is transient.